Perception of medical teachers and students regarding objective structured long examination record as an assessment tool- a prospective study - Bhalerao, Pradnya (International Journal of Research in Medical Sciences, 2017)
Background: Traditional method of assessment of a long case in practical examinations is broad based. All domains of learning are not evaluated and areas of weakness not categorised. Methods: A structured format, the objective structured long examination record (OSLER) for assessment of post graduate students in anaesthesiology for long case presentations was prepared. The impact of the new tool on the faculty, the students and the overall performance of the students was assessed through questionnaires and scoring systems. Results: We found that 75% students and 100% teachers agreed that the conduct of examination was fair. There was a 100% agreement among both that the OSLER provided an opportunity to the process of learning. 63% accepted that the questions were clear and unambiguous. 88% students agreed upon having exams conducted in a similar format in future. 75% teachers opined that they would like to take an exam in a similar form. 65% teachers agreed that more initial preparation time was needed and 58% thought that training was required. Conclusions: OSLER is a good technique for assessment of a long case in practical examination.